ANALISIS DIMENSI ETIKA DALAM PRAKTIK BISNIS SEBAGAI PILAR GOOD CORPORATE GOVERNANCE - Dian Aulya Utami; Cindy Cindy; Heri Yunus; Azhela Dwi Aryani; Ahmad Wahyudi Zein (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This study aims to analyze the dimensions of ethics in business practices and their role as a fundamental pillar of Good Corporate Governance (GCG). The background of this research is based on the increasing complexity of modern business practices, which often give rise to moral dilemmas and ethical violations due to weak ethical implementation. This research employs a qualitative approach using a library research method, with data sources consisting of textbooks, national and international journal articles, and relevant scholarly documents related to business ethics and GCG. Data analysis was conducted through content analysis to examine concepts, principles, and the relationship between ethical dimensions and the implementation of good corporate governance. The findings indicate that business ethics plays a crucial role in shaping individual, professional, and corporate behavior and serves as a moral foundation for implementing the principles of Good Corporate Governance, including transparency, accountability, responsibility, independence, and fairness. This study concludes that the successful implementation of GCG depends not only on formal regulations and systems but also on the internalization of ethical values as a sustainable organizational culture to promote integrity and long-term business sustainability.